A Secondary Data Analysis of Technology Access as a Determinant of Health and Impediment in Social Needs Screening and Referral Processes - Sara G. Bybee, PhD; Nasser Sharareh, PhD; Jia-Wen Guo, PhD; Brenda Luther, PhD; Ernest Grigorian, BS; Ching-Yu Wang, MSN; Bob Wong, PhD; Andrea S. Wallace, PhD (Elsevier, 2024)
Introduction: Although health systems increasingly integrate social needs screening and referrals into routine care, the effectiveness of these interventions and for whom they work remains unclear. Methods: Patients (N=4,608) seen in the emergency department were screened for social needs (e.g., transportation, housing, food) and offered an opportunity to receive outreach from community service specialists. Results: Among 453 patients with 1 or more social needs who requested assistance, outreach specialists connected with 95 (21.0%). Patients preferred to be contacted through their telephone (n=21, 60.2%), email (n=126, 28.0%), someone else's telephone (n=30, 6.7%), or first by telephone followed by email (n=23, 5.1%). Preferred contact method varied by patient age; endorsement of unmet transportation, housing, and utility needs; receipt of service outreach; and differences in emergency department utilization from the 6 months before the index visit to the 6 months after. Conclusions: Because limited access to a stable telephone or internet connection may prevent patients from connecting with resource referrals, social needs interventions may not benefit the most underserved populations who are at the highest risk of negative health outcomes. Future research should investigate whether communication preferences are an important indicator of needs and how to adapt social needs screening and referral processes so that they are more accessible to populations who may experience more frequent disruptions in methods utilized for digital communication.